TRANSFORMASI DAN POLA SPASIAL PERMUKIMAN PERAJIN PERAK TRADISIONAL DI DESA CELUK, GIANYAR, BALI - Ni Putu Ratih Pradnyaswari Anasta Putri; Anak Agung Raka Gunawarman; Made Suryanatha Prabawa (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2022)
The settlements of traditional silversmiths in Celuk Village, Sukawati, Gianyar cannot be separated from the influence of global modernity and the natural development of its inhabitants such as changes in population, profession, habits/lifestyle and even values. Previous research has shown that Celuk Village has potential in the context of architectural values and spatial patterns of settlements. This condition led researchers to conduct research on the transformation that occurred, both the transformation of the house and its spatial pattern. This research is a research with a qualitative approach in the scope of descriptive research. Determination of the source of this information is done by purposive sampling and snowball sampling by applying the techniques of literature review, observation and interviews in an effort to collect data. In line with the qualitative research approach, data analysis has been carried out since the beginning of data collection by verifying the relevance of the data or completing it. Descriptive data will be analyzed according to its content, to see the transformations and spatial patterns that occur in the silversmiths settlement in Celuk Village, Gianyar.